Cryptocurrencies as market singularities: the strange case of Bitcoin. Issue 5 (3rd September 2017) - Dallyn, Sam
ABSTRACT: Since its creation in 2009, the electronic currency Bitcoin has generated volumes of online debate in the business press. While there have been plenty of economic arguments situating it as a financial bubble about to collapse including from Nobel Prize winning economists, its price value has proven to be more durable than many have predicted. To explain this durability, Karpik's conception of market singularities is used to understand the Bitcoin phenomenon by outlining the beliefs that maintain Bitcoin's status as a volatile financial asset. Market singularities are markets for particular kinds of goods and services that are of uncertain and incommensurable value. Singularities markets have communities of followers and a distinctive belief system that ascribes value to a particular product, service, or asset. Developing Karpik's conception, the paper explores the libertarian political belief system that surrounds Bitcoin's status as a financial asset. I also outline some political tensions within the electronic currency community concerning governance and centralisation.